Communication Patterns of Village Children’s Forums in Promoting Child-and-Women-Friendly Villages (Case Study: The Village Children’s Forum in the Implementation of DRPPA in Indonesia) - Lila Aminullah; Fikry Zahria Emeraldien (Journal of linguistics, culture and communication, 2025)
This study aims to explore in depth the communication patterns practiced by Village Children’s Forums (Forum Anak Desa) in supporting the Indonesian government’s policy on Child- and Women-Friendly Villages (Desa Ramah Perempuan dan Peduli Anak / DRPPA). Employing a qualitative case study approach, this research combines in-depth interviews, participatory observations, and document analysis in several villages actively implementing DRPPA programs. The findings reveal that the forums apply both consensual and pluralistic communication patterns that encourage active participation, open dialogue, and decision-making based on deliberation and equality among members. Through these approaches, the forums successfully cultivate a sense of togetherness and social responsibility among village children. Nevertheless, the participatory communication process still faces several challenges, such as age limitations, lack of legitimacy among adult community members, and limited institutional support. Despite these obstacles, the Village Children’s Forums play a crucial role in strengthening DRPPA implementation through advocacy, peer education, child rights campaigns, and providing policy input to village governments. Their communication practices align with participatory communication principles and the Communication for Development (C4D) framework, emphasizing empowerment, inclusivity, and the active involvement of children as agents of change. This study highlights the importance of enhancing children’s communication capacity and institutional support to achieve more inclusive, gender-responsive, and sustainable village development.